In what sense is the notion of non-compliance with soft law objectively into the contractual law? (2019)
This research aims to analyze the non-compliance in the soft law, in the light of the new objectives postulates about the guilt (or what has been called as objective criteria of accountability). Conclusions put into question that really there is a big difference in terms of failure and guilt in the system of law of remedies of soft law and what has been called as a traditional contract law. Review of soft law texts, which have contributed to change the paradigm in continental Europe and Latin America, moving from a system based on the subjective guilt to a notion of objective fault influencing specific performance and compensation of damages. The method of work proposed is that of the legal sciences: the exhaustive analysis of doctrine and jurisprudence, mainly Spanish.